Aplicação do controle SDRE em um pêndulo invertido sobre uma plataforma móvel: controle de posição e análise de robustez - Lima, Cinara Prestes (2017)
The inverted pendulum mechanical system allows different studies of its dynamics, whereas, depending on the used parameters, it presents periodic, non-periodic and chaotic behavior. Obtaining stable controllers for this system type becomes a challenge for control designers because there is nonlinearity associated with the instability of most of their critical points. Considering this, the present work takes on as a problem the verification of the nonlinear system control possibility with a controller designed for linear system (LQR) and also the verification of the nonlinear system control possibility designed with SDRE controller when this system is gave in to parametric variations. Thereunto an applied research is developed whose objective is to design a controller considering the States-Dependent Riccati Equation (SDRE) for a nonlinear system represented by the inverted pendulum system on a movable platform in order to control the pendulum angle position and the platform positioning considering only the proportional and derivative gains from SDRE control. The analysis presented was based on the results obtained through numerical simulations in MATLAB program. From the results, it was possible to verify the controller performance.